Synthesis and characterization of carbon fibers functionalized with poly (glycidyl methacrylate) via atom transfer radical polymerization. Issue 1 (June 2015) - Wu, Yongwei; Xiong, Lei; Qin, Xiaokang; Wang, Zhengyue; Ding, Bei; Ren, Huan; Pi, Xiaolong
Abstract: In this work, polyacrylonitrile (PAN)-based carbon fibers (CF) were chemically modified with poly (glycidyl methacrylate) (PGMA) via atom transfer radical polymerization (ATRP) to improve the interaction between the CF and polymer matrix. The FT-IR, TGA, and XPS were used to determine the chemical structure of the resulting products and the quantities of PGMA chains grafted from the CF surface. The experimental results confirm that the CF surface was functionalized and glycidyl methacrylate was graft-polymerized onto the CF, and the grafting content of polymer could reach 10.2%.